2018
DOI: 10.29359/bjhpa.10.2.10
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in motives for participation in sports and exercise among Norwegian adolescents

Abstract: Background: Drawing from the theories of self-determination, this study examined how intrinsic and extrinsic motives affect Norwegian adolescents' participation in organized sports and their stamina for exercising relative to gender. We also investigated which motives can predict exercising/training, and whether this is influenced by gender.Material/Methods: 368 students (male, 51%; female 49%) aged between 16 and 18 years completed a standardized questionnaire "Motives for Physical Activity Measure -Revised (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 27 publications
2
6
0
Order By: Relevance
“…Our results also match those presented by other studies, which highlighted fun and wellbeing as the greatest incentives when exercising [21,49]. In relation to the differences in motivation for boys and girls for practicing physical exercise, our study agrees with the conclusions of Jakobsen and Evjen, who found that intrinsic motives influenced sustained exercise in adolescents [50].…”
Section: Discussionsupporting
confidence: 92%
“…Our results also match those presented by other studies, which highlighted fun and wellbeing as the greatest incentives when exercising [21,49]. In relation to the differences in motivation for boys and girls for practicing physical exercise, our study agrees with the conclusions of Jakobsen and Evjen, who found that intrinsic motives influenced sustained exercise in adolescents [50].…”
Section: Discussionsupporting
confidence: 92%
“…Of these, being strong and vigorous or feeling active were the most indicated, reaffirming studies that point to adolescence as the stage where motor competence is consolidated, which is associated with the improvement of healthy aspects, such as weight, cardiorespiratory capacity, and strength [41,63]. Such a description contrasts and complements other studies that previously indicated other types of motives, such as those made by Moreno-Murcia, Cervelló, Huéscar, and Llamas [64] that pointed to fun, being with friends, and a enjoying practice, or that of Gómez-López, Ruiz-Juan, García-Montes, Granero-Gallegos, and Piéron [65], who showed that there was no single reason to maintain active behavior due to the motivations being of an intrinsic nature, such as pleasure, health, and, most importantly, evasion. Rhodes and Kates [66] pointed out, after a systematic review, the relevance of affective involvement as the main source of motivation, while others such as Goguen-Carpenter et al [67] and Jakobsen and Evjen [68] highlighted the interest, enjoyment, and feeling of competence as the most important elements for the practice of physical exercise in childhood and adolescence.…”
Section: Discussionsupporting
confidence: 60%
“…Generally, most studies confirm higher PA motivation among boys compared to girls, in both adolescents [ 41 ] and young adults [ 42 ]. However, a Norwegian study showed that girls had higher scores in intrinsic motives for sports participation, compared to boys, and that boys had higher scores in more extrinsic motives, but gender had no influence on motivation for sustained exercise [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar conclusions were also formulated in a longitudinal study by Abi Nader et al [ 39 ], who recommended that focus should be highlighted on enjoyment and competence motives in order to increase MVPA. According to Jakobsen and Evjen [ 43 ], intrinsic motives such as enjoyment and competence are vital for sustained exercise in Norwegian adolescent boys and girls. However, it also turns out that interventions to increase motivation for PA in schools may boost PA enjoyment motives, especially in girls [ 5 ].…”
Section: Discussionmentioning
confidence: 99%